Studies on ion selectivity of parchment impregnated Ba(II) molybdate artificial membrane - Ansari, Afren; K. Shukla, A.; Ayub Ansari, Mohd. (International Journal of Advanced Chemistry, 2022)
Parchment impregnated Ba(II) molybdate artificial membrane was prepared by the ion-interaction method using BaCl2 and Na2MoO4 solutions. The prepared membrane was characterized by sophisticated instrumental techniques such as Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), Fourier-transform infrared (FT-IR) spectroscopy, Thermogravimetric analysis (TGA)/Differential thermal analysis (DTA), X-ray diffraction (XRD) and Energy dispersive X-ray (EDX) analysis. The artificial membrane was tested for its antimicrobial activity against Gram-negative (Escherichia coli and Pseudomonas aeruginosa) and Gram-positive (Staphylococcus aureus) microorganism. The effective fixed charge density of the prepared membrane has been used individually to calculate theoretical bi-ionic potentials (BIP) and compared with experimentally determined values of bi-ionic potential. The selectivity of ions for the membrane has been found as K+>Na+>Li+ which on the basis of the Eisenman-Sherry model of membrane selectivity, points towards the low field strength of the charge groups joined to the membrane matrix. Membrane conductance values has also been experimentally determined.Â Â